The determination of 3-methoxy 4-hydroxy mandelic acid in urine - Woiwod, A. J. (1961)
A simple and accurate method for determining 3-methoxy 4-hydroxy mandelic acid in urine is described. The amounts excreted in urine in 24 hours by nine normal subjects and three patients with phaeochromocytoma have been determined.